Gerenciamento de Dados Multimídia: Desenvolvimento de uma ferramenta para o gerenciamento de acervos de museus acadêmicos - Kurtz, Kellerson; Santi, Bruno; Sias, Jonathan; Halmenschlager, Pedro; Peske, Mauricio; Tavares, Tatiana (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
Multimedia applications involve the development of tools for creating and digitizing multimedia contents and their distribution through communication networks. Tools that appear in different domains of application and offer services increasingly present in our daily life. For example, museum spaces that use the digital medium as an expansion of their physical limits. This paper presents a tool for managing digital collections of academic museums. The tool allows the user, at different levels, the manipulation of collections and their parts. In addition to facilitating the management of content, the tool feeds the database available to the general public, thus acting in the dissemination of content.